Tufting enteropathy with EpCAM mutation: case report - Karla Lais Pêgas; Eduardo Cambruzzi; Regis Schander Ferrelli; Carolina Soares da Silva; Renata Rostirola Guedes; Marina Adami; Eduardo Montagner Dias; Melina Utz Melere; Marilia Rosso Ceza; Cintia Steinhaus; Matias Epifanio; Julie Salomon; et al. (Sociedade Brasileira de Patologia Clínica, 2014)
Tufting enteropathy (TE), also known as intestinal epithelial dysplasia (IED), is a rare congenital enteropathy related to an earlyonset of severe intractable diarrhea due to specific abnormalities of the intestinal epithelium and mutations of the EpCAM gene. TE is characterized by clinical and histological heterogeneity, such as with low or without mononuclear cell infiltration of the lamina propria, and abnormalities of basement membrane. TE can be associated with malformations, other epithelial diseases, or to abnormal enterocytes development and/or differentiation. The authors report a case of a Brazilian child with TE associated with c.556-14A>G mutation in the EpCAM gene (NM_002354.2).